Peningkatan Hasil Belajar Pecahan Menggunakan Pendekatan Pendidikan Matematika Realistik Di Sekolah Dasar - Erta, Yossi; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research goals is to description enhancement fractional learning outcomes using realistic mathematical education approach (PMR) in class IV SDN 21 Pakan Sinayan. This type of research is Classroom Action Research with qualitative and quantitative approaches. The research subjects were teachers and 20 students in class IV SDN 21 Pakan Sinayan. The study was conducted in two cycles the first cycle two meetings and the second cycle one meeting. The result showed an increase, result of observed learning plans of the first cycle 80% increased in the second cycle to 92% (AB), observations of teachers the first cycle 79% (B) increased in the second cycle to 93% ( AB), observations of student the first cycle 73%  (B) increased in the second cycle to 90%, and the average assessment of student learning outcomes the first cycle 74 increased in the second cycle to 88. Keywords: Learning Outcomes, Realistic Mathematics Education Approach